Effect of high pressure treatment on properties and nano–Ag migration of PLA-based food packaging film. (July 2019) - Fan, Chunli; Cui, Rui; Lu, Wangwei; Chen, Haiyan; Yuan, Minglong; Qin, Yuyue
Abstract: The effects of nano-Ag content, high pressure treatment, and migration time on nano-Ag migration and properties of polylactide (PLA)/nano-Ag composite films were investigated. The PLA films incorporated with 1 wt%, 5 wt%, 10 wt%, 15 wt%, and 20 wt% nano-Ag were treated by 100, 200, 300, and 400 MPa high pressure for 10, 20, and 30 min, respectively, and then soaked in isooctane food simulant at 40 °C for 49 days. The migration of nano-Ag in the PLA nanocomposite films increased by the addition of nano-Ag, the pressure of high pressure treatment, and migration time. Thermal and mechanical properties showed that high pressure and migration time would make the films rougher and increase the crystallization temperature of the PLA nanocomposite films. Moreover, the addition of nano-Ag could improve the barrier properties of the PLA nanocomposite films. However, the longer the migration time, the worse the barrier property. The results indicated that the migration amount of nano-Ag and performance of the PLA/nano-Ag composite films were greatly affected by the migration time. Highlights: This paper applied high pressure technology to the preparation of composite film materials. The addition of nano-Ag could increase the crystallinity of the composite films. The migration of the nano-Ag/PLA composite films in the oily food simulating liquid was safe. As the migration time increased, the barrier and mechanical properties of the composite films deteriorated. The results indicated that the migration of nano-Ag in the composite films increased as the initial addition quantity of nano-Ag.